Prosecuting child soldiers in the arab world: between the state, society, and retributive and restorative justice - Hasona, Yousra Ibrahim (Contemporary justice review, 2022)
The phenomenon of child soldiers in the Arab World could threaten peace and stability in the post-conflict phase. Many of these children committed crimes against their society such that some communities reject them and demand their prosecution, with no real attention from both the political and the academic level, consequently, child soldiers are treated as criminals. This article, based on 16 interviews with academic and legal experts between 2020–2021, aims to analyzes and present how restorative justice can be used as an alternative approach to retributive justice in addressing child soldiers’ criminal responsibility. The findings show that restorative justice can address child soldiers’ responsibility in a way that ensures restore their relationships with their community and reintegrate them without stigmatization.